Observation of spin-orbit effects with spin rotation symmetry - Alisha M. Humphries (Nature Portfolio, 2017)
Converting charge to spin currents using spin–orbit interactions has useful applications in spintronics but symmetry constraints can limit the control over spin polarization. Here the authors demonstrate spin–orbit effects with a different symmetry, which could help generate arbitrary spin polarizations.